Efektivitas Program Kelambunisasi di Puskesmas Oesapa Kecamatan Kelapa Lima Kota Kupang - Monika Bonlay; Rinawaty Sirait; Serlie K. A. Littik (Lontar : Journal of Community Health, 2019)
The program for routine insecticide-treated bed nets is one of the government's efforts to reduce malaria morbidity. The research objective was to describe the effectiveness of the routine insecticide-treated bednet distribution program in the context of reducing malaria morbidity in Oesapa Health Center, Kelapa Lima District, Kupang City in 2018. Descriptive survey research with a qualitative approach. Informants in this study amounted to 3 people and 65 families as observation samples. The research instrument uses interview guidelines. The results of the study show 1) Input; health workers and facilities were limited (cars and motorbikes), particularly in distributing the nets to pregnant women, infants, children under five, and children. 2) Process; The program was planned by The Health Office of Kupang City while implementation and evaluation was taken by health workers from Oesapa Health Center. Barriers were related to low accessibility in reaching the targeted house in need, inadequate number of health staff, and unavailability of special facility needed to distribute the nets 3) Output; A total of 188 nets was distributed to the target according to the program goal. Based on observations from 65 households that became the study sample, 63 households used and treated kalambu with insecticides until 2019. The distribution of insecticide-treated bed nets was considered ineffective. Health workers and facilities need to be provided adequately to distribute the nets and monitoring is necessary to guarantee the distribution reaching the target.